Specialty Probation Officers as Street-Level Bureaucrats: Exploring How Discretion Is Perceived and Employed on a Mental Health Caseload - Terpstra, Brice (International journal of offender therapy and comparative criminology, 2022)
This study explores the perceptions of specialty mental health caseload probation officers and their use of discretion in day-to-day supervision of individuals with mental illness in one large jurisdiction in the United States. Scholars have examined overall effectiveness of specialty probation programs, probation officers’ roles as street-level bureaucrats, and the impact of the mental health caseload probation officer and probationer relationship on successful completion. Less attention, however, has been placed on examining how the officers supervising these specialty caseloads perceive their roles as mental health probation officers and how they use discretion in their caseload management. The current study examines the narratives of 24 specialty mental health caseload probation officers and supervisors to understand how discretion is used on a problem-solving caseload and how discretionary decision-making may impact probationer outcomes.